Resenha de: Miracle at Joaseiro - Kuhl, Júlio Cesar Assis (Revista de História, 1975)
DELLA CAVA (Ralph) . — Miracle at Joaseiro.  New York and London. ColumbiaUniversity Press, 1970 (Institute of Latin American Studies— Columbia University) 324 p. 23 cm.